1998
DOI: 10.1016/s0368-2048(98)00189-3
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric sensitivity of the C 1s spectra of xylenes

Abstract: Oscillator strengths for C 1s inner-shell excitation of the isomeric xylenes (ortho-, meta-and para-) have been derived from electron energy loss spectra recorded under scattering conditions dominated by electric dipole transitions. The lineshape of the C 1s → p* transition is found to be dependent on the substitution pattern, with para-xylene exhibiting two components, orthoxylene a single asymmetric peak, and meta-xylene a single symmetric peak at an instrumental resolution of 0.35 eV. Improved virtual orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They found all three isomers were essentially identical with only minor differences. Inner shell excitation of the C 1s orbital was made by Eustatiu et al [16], who observed very similar spectra for all three isomers. Similar observations for the total ionization cross section of the isomers of xylene was made by Jiao and…”
Section: Introductionmentioning
confidence: 65%
“…They found all three isomers were essentially identical with only minor differences. Inner shell excitation of the C 1s orbital was made by Eustatiu et al [16], who observed very similar spectra for all three isomers. Similar observations for the total ionization cross section of the isomers of xylene was made by Jiao and…”
Section: Introductionmentioning
confidence: 65%
“…The calculated excitation energies, ionization potentials, term values, and oscillator strengths are listed in Table . There is a large body of previous computational work for many of these species, including ab initio IVO calculations of dimethyl terephthalate, N -phenylcarbamic ethyl ester, N , N ‘-diphenyl urea, and p -xylene, as well as extended Hückel MO calculations of benzaldehyde, benzoic acid ethyl ester, terephthaldehyde, benzene-1,4-diol, and phenol . We have repeated these calculations here with a common basis set to permit a systematic comparison of experiment to theory.…”
Section: Resultsmentioning
confidence: 99%
“…In the MDI polymers, each phenyl ring is bonded to one amide group and one methylene group; while in the TDI polymer, each phenyl ring is bonded to two amide groups and one methyl group. The C 1s spectra of xylenes demonstrate that the C−R shift due to methyl substitution is very small (∼0.1 eV) . Therefore, the methylene C−R shift can be neglected and only the amide C−R shifts are significant.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s spectra of xylenes demonstrate that the C-R shift due to methyl substitution is very small (∼0.1 eV). 21 Therefore, the methylene C-R shift can be neglected and only the amide C-R shifts are significant. In MDI-based polymers, one phenyl carbon will have the C-R shift and five phenyl carbons will not; in the TDI-based polymers, two phenyl carbons will have the C-R shift while four carbons will not.…”
Section: Introductionmentioning
confidence: 99%